2020
DOI: 10.1101/2020.02.11.944819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adapting CRISPR/Cas9 System for Targeting Mitochondrial Genome

Abstract: Gene editing of the mitochondrial genome using CRISPR-Cas9 system is highly challenging mainly due to sub-efficient delivery of guide RNA and Cas9 enzyme complexes into mitochondria. In this study, we were able to perform gene editing in the mitochondrial DNA by appending NADH-ubiquinone oxidoreductase chain 4 (ND4) targeting guide RNA to a RNA transport derived stem loop element (RP-loop) and expressing the Cas9 enzyme with preceding mitochondrial localization sequence. Our results showed mitochondrial coloca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…A recent preprint study reported the editing of the MT-ND4 gene accomplished by targeting the guide RNA to an RNA transport derived stem loop element (RP-loop), while expressing the Cas9 enzyme with a mitochondrial localization sequence [ 363 ]. However, due to the controversial nature of mammalian mitochondrial RNA import [ 364 ], the use of the CRISPR/Cas9 application for mtDNA editing is still debated.…”
Section: Precision Medicine Approaches For Pmd Caused By Mtdna Defmentioning
confidence: 99%
“…A recent preprint study reported the editing of the MT-ND4 gene accomplished by targeting the guide RNA to an RNA transport derived stem loop element (RP-loop), while expressing the Cas9 enzyme with a mitochondrial localization sequence [ 363 ]. However, due to the controversial nature of mammalian mitochondrial RNA import [ 364 ], the use of the CRISPR/Cas9 application for mtDNA editing is still debated.…”
Section: Precision Medicine Approaches For Pmd Caused By Mtdna Defmentioning
confidence: 99%
“…A recent study showed that gRNAs with short hairpin structures can promote mitochondrial import and specific cleavage of mitochondrial DNA, albeit at low levels because of limited import into the mitochondrial matrix ( Loutre et al., 2018 ). More recently, Hussain et al. (2020) demonstrated that gRNA could be efficiently imported to the mitochondria of mammalian cells with an additional 20-bp stem–loop element of nuclear RNase P in a polynucleotide phosphorylase-dependent manner ( Wang et al., 2010 ).…”
Section: Toward Molecular Breeding Through Mitochondrial Genome Modificationmentioning
confidence: 99%
“…Because all three intronic sequences do not include any known miRNAs or predicted stem-loop structures, they seem to act in trans as long ncRNA regulatory elements [20]. Similarly, constructs containing common selection markers/reporter genes like GFP, EGFP, Neo r , LacZ, and DsRed are often left within the target genome postselection [9,21,29,37,62]. However, these genes themselves can become potential targets of miRNAs of host origin, e.g., Mus musculus as discussed later.…”
Section: The Problemmentioning
confidence: 99%
“…Neomycin resistance gene (Neo r ) is one of the widely utilized selection markers for the cells which are correctly targeted, and the neomycin cassette itself is normally left within the genome post-selection, assuming that it has no adverse effect on the eukaryotic cell biology [21,50,62]. But upon careful observation, it can be seen that the Neo r gene construct itself is a potential target of several miRNAs of the eukaryotic origin or more specifically the miRNAs within the cells of the neomycin cassette containing transgenic mice (Table 1).…”
Section: Commonly Used Foreign Genes Targeted By Mus Musculus Mirnasmentioning
confidence: 99%